Building a developmental culture of feedback. Issue 2 (9th January 2018) - Drago-Severson, Ellie; Blum-DeStefano, Jessica
Abstract : Purpose: This paper draws from more than 25 years of research with aspiring and practicing educational leaders to present six strategies for building a culture of feedback in schools, teams, districts, professional learning opportunities, and other educational settings. These strategies reflect key elements of the authors' new, developmental approach to feedback. The paper aims to discuss these issues. Design/methodology/approach: Through the lens of adult developmental theory, the authors highlight foundational learnings from open-ended survey research with 14 educational leaders about their experiences giving and receiving feedback, and prior qualitative, mixed-method, and longitudinal research with principals, assistant principals, teachers, superintendents, and other educational leaders. Findings: The authors share six developmentally oriented strategies for establishing trust and building conditions for authentic, generative feedback: finding value in mistakes, modeling vulnerability, caring for the (inter)personal, clarifying expectations, sharing developmental ideas, and building an infrastructure for collaboration. Practical implications: This work has implications for leadership and leadership preparation, especially given contemporary emphases on collaboration and high-stakes evaluations as tools for ongoing improvement, enhancing professional capital, and internal, individual, and system-wide capacity building. Originality/value: Because a developmental perspective has been noticeably missing from the wider feedback literature and leadership preparation curricula, this work extends and enhances tenets from different fields (e.g. business, developmental psychology, educational leadership and educational leadership preparation), while also addressing urgent calls for educational reform; leadership preparation, development, and practice; and professional capital building.